2015
DOI: 10.1186/1471-2164-16-s13-s5
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-related known and candidate SNP markers can significantly change affinity of TATA-binding protein for human gene promoters

Abstract: BackgroundObesity affects quality of life and life expectancy and is associated with cardiovascular disorders, cancer, diabetes, reproductive disorders in women, prostate diseases in men, and congenital anomalies in children. The use of single nucleotide polymorphism (SNP) markers of diseases and drug responses (i.e., significant differences of personal genomes of patients from the reference human genome) can help physicians to improve treatment. Clinical research can validate SNP markers via genotyping of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 130 publications
(191 reference statements)
0
24
0
1
Order By: Relevance
“…The human LEP gene (leptin; synonyms: obesity factor with acronym OB ) contains a candidate SNP marker (rs201381696) of obesity (reducing this gene’s expression) as well as candidate SNP markers (rs200487063 and rs34104384) of obesity-induced hypertension caused by overexpression of this gene as we have predicted in silico and verified in vitro in our previous work [66] (Table 4). …”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…The human LEP gene (leptin; synonyms: obesity factor with acronym OB ) contains a candidate SNP marker (rs201381696) of obesity (reducing this gene’s expression) as well as candidate SNP markers (rs200487063 and rs34104384) of obesity-induced hypertension caused by overexpression of this gene as we have predicted in silico and verified in vitro in our previous work [66] (Table 4). …”
Section: Resultsmentioning
confidence: 57%
“…In addition, a clinical case review [143] revealed longer survival in aggressive leptin-deficient women with anorexia nervosa. On the basis of these data, we expanded our prediction [66] on the obesity-related candidate SNP markers rs201381696, rs200487063, and rs34104384 to our prognosis that these SNPs can also be candidate SNP markers of aggressiveness in obesity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper by Arkova et al "Obesity-related known and candidate SNP markers can significantly change affinity of TATA-binding protein for human gene promoters" [10] (http://www.biomedcentral.com/1471-2164/16/S13/S5) presents an in silico analysis of 22 known nucleotide polymorphisms and arrived at functionally important conclusion about the mechanism of action for at least one of these DNA variants.…”
Section: Bmc Genomicsmentioning
confidence: 99%
“…Recently, we showed suitability of this Web service for prediction of candidate SNP markers of complications of Mendelian diseases in obesity [38] and of autoimmune complications of these diseases [39] as well as SNP markers that can either enhance or weaken biological activity of oncogene inhibitors during cancer chemotherapy [40] (hereinafter, we use the term “Mendelian disease” according to the notation in database Online Mendelian Inheritance in Man, OMIM® [28]).…”
Section: Introductionmentioning
confidence: 99%